KEMISKINAN DI KOTA BENGKULU, APA PENYEBABNYA? - Nugraha, Dian Putra (Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
Since 2011, poverty in Bengkulu City has been indicated as very high, far above the poverty of Bengkulu Province's and Indonesia's poverty, but there have been very small amount of re-searches related to the causes of this poverty. This study aims to identify the causes of poverty in Bengkulu City through descriptive analysis on the structure of poor population in Bengkulu City. The results show that poverty in Bengkulu City is influenced by the existence of unem-ployed citizens, while higher education level cannot be a guarantee for avoidance from poverty. Keywords: Bengkulu City, Characteristics, Expertise, Idleness, Poor